Development of Smart Plant Watering System Application Based on Internet of Things - Bachtiar, Adnan Nuur; Faisal, Mochammad; Darwis, Muhammad (Universitas Trilogi, 2025)
In 2024, air pollution levels in Jakarta were recorded as the highest in Southeast Asia, based on various air quality monitoring reports. This condition has become an increasingly alarming environmental issue, with pollution levels frequently exceeding the safe threshold set by the World Health Organization (WHO). One of the efforts by the Jakarta Provincial Government to address this problem is a free plant distribution program for the public. Plants play a crucial role in absorbing carbon dioxide, producing oxygen, and reducing airborne pollutant particles. However, plant maintenance—especially watering—poses its own challenges. Inefficient watering can cause plants to experience stress, wilt, or even die. With the advancement of technology, an automatic plant watering system based on the Internet of Things (IoT) presents a potential solution to improve the efficiency and sustainability of plant care. This study aims to develop a smart plant watering system application based on IoT that can automatically control watering based on real-time soil moisture levels. The system was applied to spider plants (Chlorophytum comosum) grown in pots with a diameter of 15 cm. By using an ESP32 microcontroller, a soil moisture sensor (Capacitive Soil Moisture Sensor v1.2), an air temperature and humidity sensor (DHT11), and a water pump, the system automatically activates watering when the soil moisture is below 55% and stops when it exceeds 65%. Sensor data is stored in a database and displayed through a web-based application for remote monitoring.